A new photosensory function for simple photoreceptors, the intrinsically photoresponsive neurons of the sea slug Onchidium - Gotow, Tsukasa; NISHI, Takako (Frontiers in Cellular Neuroscience, 2009)
Simple photoreceptors, namely intrinsically light-sensitive neurons without microvilli and/or cilia, have long been known to exist in the central ganglia of crayfish, Aplysia, Onchidium, and Helix. These simple photoreceptors are not only first-order photosensory cells, but also second-order neurons (interneurons), relaying several kinds of sensory synaptic inputs. Another important issue is that the photoresponses of these simple photoreceptors show very slow kinetics and little adaptation. These characteristics suggest that the simple photoreceptors of the Onchidium have a function in non-image-forming vision, different from classical eye photoreceptors used for cording dynamic images of vision. The cited literature provides evidence that the depolarizing and hyperpolarizing photoresponses of simple photoreceptors play a role in the long-lasting potentiation of synaptic transmission of excitatory and inhibitory sensory inputs, and as well as in the potentiation and the suppression of the subsequent behavioral outputs. In short, we suggest that simple photoreceptors operate in the general potentiation of synaptic transmission and subsequent motor output; i.e., they perform a new photosensory function.